Metsämaisemarakenteen muutokset Karjalankannaksella - Takala, Terhi (Helsingfors universitet, 2007)
The biodiversity in Finland is dependant on the vast forest areas in Russia and Karelian Isthmus acts as an important ecological corridor which connects these forests together. However, Karelian Isthmus is also important for the forest industry and increasing forest use has caused concerns of the effects forest cuts have on the biodiversity of the area. The purpose of this study was to examine how the forests in the Karelian Isthmus have changed in the past 20 years. Special attention was given to the changes of the landscape structure and regional differences. The study was based on the data from a field survey and Landsat satellite images. After image registration the satellite images were normalized using linear regression method. This was done in order to calibrate the radiometric differences in the images. The interpretation of the images was done using supervised classification. The training areas used in classification were based on the ground truthing data collected during the field work. Two classifications were done to each image and four forest types were used: spruce, pine, mixed and deciduous forest. In the more detailed classification the forest types were further divided into young and old forests. The accuracy of the classification was assessed using reference data and contingency tables. The detailed classification was clearly less accurate and only the simple classification without the age classes was used in the following analyses. For estimating the changes in the forest structure at the landscape level, landscape metrics were calculated from the classified images. Five landscape indices were used in this study: class area (forest type area), number of patches, mean patch size, edge density and mean nearest neighbour. According to the interpretation of the satellite images the total forest area in the Karelian Isthmus has increased 4 %. Forest area of the mixed forest and especially deciduous forest had increased. Spruce forests had decreased 34 % and pine forests 25 % but these meant only 4 ...